CHARACTERIZATION AND TOXICITY TEST OF PUFFER FISH FROM PAMEUNGPEUK WATERS, WEST JAVA - Eka Deskawati; Sri Purwaningsih; Purwanti Ningsih (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
A puffer fish contains a secondary metabolite toxic called tetrodotoxin (TTX), which can be used as an anesthetic and medication to relieve chronic pain for cancer patients. The purposes of this study were to determine the LC50 value and chemical composition of extracts from various tissues of puffer fishes as a first step to determine the further isolation of tetrodotoxin. In this study various tissues from meat, liver, skin, heart, and ovary of Arothron hispidus and Diodon hystrix species were extracted, characterized, and tested levels of toxicity using Brine Shrimp Lethality Test (BSLT) methods. Between the two puffer fishes studied, the highest toxicity was found in Arothron hispidus ovary with LC50 value of 29.65 ppm. Chemical constituents of the ovary were alkaloids, carbohydrates, and amino acids. Toxic compounds found in the extracts of puffer fish ovaries were tetrodotoxin which is a compound of the alkaloid class of secondary metabolites. Keywords: Puffer fish, Arothron hispidus, Diodon hystrix, toxicity, Brine Shrimp Lethality Test